Developing Edupreneurship-Oriented Natural and Social Sciences Teaching Materials Using the Project-Based Learning to Improve Students' Creativity for Primary School - Adlan Surya Saputra; Agus Sutono; Ida Dwijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The intent of this study is to describe the validity, practicality, and effectiveness of edupreneurship-oriented IPAS teaching materials using the PjBL model to improve primary school students' creativity. The research design used is ADDIE, which includes analysis, design, development, implementation, and evaluation. This research was conducted at public primary school Wonokerso 2. The data collection instruments used are validity sheets, teacher and student response questionnaires, and student creativity test sheets. The results of the study indicated that the validity test carried out by experts had a value of 90.57, which met the very valid category. The practicality test results from the student questionnaire, class teacher responses, and colleagues' evaluations, which had average values of 90.74, 87.10, and 84.68, respectively, all met the very practical category. The effectiveness test was based on the results of the paired sample t-test (value of Sig. 0.00 < 0.05) and n-gain tests (value of 0.52). The results of the paired sample t-test on student creativity showed an average difference between the observation data before and after the study. The n-gain analysis indicates that students' creativity meets the moderate category. The results of the study indicate that the entrepreneurship-oriented IPAS teaching materials using the PjBL model developed are proven to be valid, practical, and effective in supporting character education